Prevalence Of Diabetic Foot Ulcers In Patients With Type 2 Diabetes Mellitus - Vikram, Muh; Iskandar, Darariani; Ardiyanto, Ardiyanto; Hasan, Hasan; Nur, Muh Jabal (Newinera Publisher, 2024)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels. Approximately 422 million people worldwide suffer from diabetes, with a high prevalence in low- and middle-income countries. According to the 2018 consensus of the Indonesian Endocrinology Association (PERKENI), the prevalence of diabetes in individuals aged ≥15 years is 2%. This research is a descriptive retrospective study with a cross-sectional approach aimed at describing the characteristics of diabetic foot ulcer patients in the outpatient unit. Data was obtained from the medical records of Ibnu Sina Hospital, with a sample size of 88 patients. Based on the research findings, diabetic foot ulcers are more commonly found in women (61.4%), as well as in individuals with normal nutritional status (55.7%) and those in the hypertension grade 1 group (58.0%). Most patients have a final education level of elementary school or equivalent (44.3%) and work as housewives (40.9%). The majority of diabetic foot ulcer patients are from the late elderly age group (56–65 years) and are female. Most of the patients had normal nutritional status, grade 1 hypertension, an elementary school or equivalent education, and worked as housewives.